PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN AKUNTANSI TERHADAP KETERANDALAN LAPORAN KEUANGAN - Intan Kurniawati, Rispantyo Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this research is to analyze the significance of the influence of the quality of human resources, utilization of information technology and accounting internal control system against reliability the financial report on the Agency's Revenue Management Asset and financial Area of the city of Surakarta. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research is the Population in this research Revenue Agency financial management employees and assets of the Surakarta Area totalling 84 employees, the number of samples that used as many as 84 people, so this research is Census research. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, and multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that the quality of human resources, utilization of information technology and accounting internal control system a positive significant effect against the reliability the financial report on the Agency's Revenue Management Asset and financial Area of the city of Surakarta.Keywords: quality of human resources, utilization of information technology, accounting, internal control system, reliability financial statements